PENGARUH SUMBER DAYA MANUSIA DAN MODAL TERHADAP PROSES PRODUKSI DI SCTV - Diajeng Reztrianti (Jurnal Ekonomi dan Industri, 2022)
One of the media in mass communication that has the greatest influence on the formation of public opinion is television. Television can provide a variety of information so that it can be used by the public in completing their knowledge. In order to present television programs that attract public interest, a good television program is needed to entertain the public. Factors that support this interesting television program are human resources, capital, and the production process.